A review on the pharmacotherapy and case studies of hypercalciuria and hyperoxaluria - Lika Ginanti Febriana&, Sri Adi Sumiwi, Jutti Levita (Journal of Applied Pharmaceutical Science, 2022)
The association of various pathological conditions such as nephrolithiasis and bone destruction with hypercalciuria and hyperoxaluria leads to the need for comprehensive studies to support therapy. This review aims to find the best therapy for these diseases by studying case reports. The method used was by tracing articles in two databases, PubMed and Google Scholar, using the keywords “Hypercalciuria,” “Hyperoxaluria,” “Pathophysiology,” “Calcium Homeostasis,” “Oxalate Homeostasis,” “Diagnosis,” “Pharmacotherapy,” and “Case Report”. The initial screening resulted in 640 articles, and only 54 articles were included in this study. The pathophysiology of hypercalciuria and hyperoxaluria is related to abnormalities that occur in the kidneys, intestines, and bones. Hypercalciuria and hyperoxaluria are related to the development of urinary calculi. In general, the diagnosis of both can be made by measuring calcium and oxalate levels in urine at 24 hours, blood tests, and other investigations. Based on the case studies, pharmacotherapy which is given to minimize the symptoms of hypercalciuria was hydrochlorothiazide, chlorthalidone, and bendroflumethiazide, while hyperoxaluria was treated with pyridoxine, alkaline citrate, magnesium supplementation, calcium supplementation, and other adjunctive therapies.
Keywords: Calcitriol, calcium stones, homeostasis, hypercalciuria, hyperoxaluria, urinary calculus